2017
DOI: 10.1080/01443410.2017.1359239
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the written characters orientation and its influence on digit reversal by children

Abstract: Recent research has found that children reverse mainly the leftoriented characters when writing from memory (e.g. they write ɩ and ε instead of J and 3). In order to obtain an objective definition of the left-orientation of a character, the ratings of the level of leftorientation of all the asymmetrical capital letters and digits by 142 adult students was analysed in Study 1. Study 2, on 298 five-sixyear-old children, examined an immediate prediction of Study 1, namely that the children reverse mainly the digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The correlation between the frequencies of reversal of the characters in the two groups was very strong, r(21) = 0.962. A further study confirmed the lack of a qualitative difference between reversal in the two groups but suggested a slightly greater frequency of reversal in children who wrote with the left hand [38] (see also [35], Expt 1a).…”
Section: Children Who Write With the Right Hand Reverse The Charactermentioning
confidence: 81%
See 4 more Smart Citations
“…The correlation between the frequencies of reversal of the characters in the two groups was very strong, r(21) = 0.962. A further study confirmed the lack of a qualitative difference between reversal in the two groups but suggested a slightly greater frequency of reversal in children who wrote with the left hand [38] (see also [35], Expt 1a).…”
Section: Children Who Write With the Right Hand Reverse The Charactermentioning
confidence: 81%
“…We do not exclude that the absence of orientation can in fact result from two differently oriented representations, perhaps one in each hemisphere [60], whose accesses are random or determined by situational or cultural constraints. However, the analysis for the digits [38], on the basis of a character feature set [71], suggests rather a single representation. Because it has no orientation, this representation cannot help a child decide how to orient a character when he or she has to write it from memory (under dictation) or choose between a correctly written character and its mirror image.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations